2018
DOI: 10.1111/pbi.12918
|View full text |Cite
|
Sign up to set email alerts
|

Integrating GWAS and gene expression data for functional characterization of resistance to white mould in soya bean

Abstract: SummaryWhite mould of soya bean, caused by Sclerotinia sclerotiorum (Lib.) de Bary, is a necrotrophic fungus capable of infecting a wide range of plants. To dissect the genetic architecture of resistance to white mould, a high‐density customized single nucleotide polymorphism (SNP) array (52 041 SNPs) was used to genotype two soya bean diversity panels. Combined with resistance variation data observed in the field and greenhouse environments, genome‐wide association studies (GWASs) were conducted to identify q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 56 publications
5
56
0
Order By: Relevance
“…Comparing the similarity of two genes' expression profiles, or coexpression, quantifies the joint response of the genes to various biological contexts, and highly similar expression profiles can indicate shared regulation and function (Eisen et al, 1998). The analysis of coexpression has been used successfully to identify functionally related genes, including in several crop species (Ozaki et al, 2010;Mochida et al, 2011;Swanson-Wagner et al, 2012;Zheng and Zhao, 2013;Obayashi et al, 2014;Sarkar et al, 2014;Schaefer et al, 2014;Michno et al, 2018;Wen et al, 2018), and has been used to characterize GWAS results in Arabidopsis (Arabidopsis thaliana) (Chan et al, 2011;Corwin et al, 2016;Angelovici et al, 2017;Lee and Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the similarity of two genes' expression profiles, or coexpression, quantifies the joint response of the genes to various biological contexts, and highly similar expression profiles can indicate shared regulation and function (Eisen et al, 1998). The analysis of coexpression has been used successfully to identify functionally related genes, including in several crop species (Ozaki et al, 2010;Mochida et al, 2011;Swanson-Wagner et al, 2012;Zheng and Zhao, 2013;Obayashi et al, 2014;Sarkar et al, 2014;Schaefer et al, 2014;Michno et al, 2018;Wen et al, 2018), and has been used to characterize GWAS results in Arabidopsis (Arabidopsis thaliana) (Chan et al, 2011;Corwin et al, 2016;Angelovici et al, 2017;Lee and Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The GWAS approach has been demonstrated in soybean ( Glycine max Merr. L.) resistance to S. sclerotiorum where numerous single nucleotide polymorphisms (SNPs) associated with this quantitative resistance were discovered (Bastien, Sonah, & Belzile, ; Moellers et al., ; Wen et al., ; Wu, Zhao, Liu, et al., ). However, mapping results may discover SNPs that locate in intergenic genomic regions, and the interpretation of a confidence interval relies on the size of linkage disequilibrium (Bush & Moore, ).…”
Section: Introductionmentioning
confidence: 99%
“…RNA‐Seq and GWAS both have their advantages, and combining them provides a powerful tool to discover not only active genes that express in response to treatments, but also genetic diversity and SNPs associated with the treatment. This combined strategy has been applied to understand white mold resistance and yields in B. napus (Lu et al., ; Wei et al., ) and soybean (Wen et al., ), but not in pea. Because genes that can be found by both GWAS and RNA‐Seq will have higher potential in contributing to white mold resistance, this study aimed to understand and compare the genetics of lesion and nodal resistance by applying both GWAS and RNA‐Seq approaches in the pea‐ S. sclerotiorum pathosystem.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified 282 eQTNs associated with the expression of 18 genes, and these eQTNs represent 100 gene–gene pairs, which highlights the complexity of the regulatory network (Figure S7). PtoPsbY expression was significantly associated with 17 genetic factors; similarly, PtoLhcb4.2 regulates the expression of eight genes, providing an illustration of the power of eQTN mapping for identifying active regulatory factors in the complex photosynthetic pathway (Wen et al , ). The direct integration of eQTNs with quantitative trait analyses has facilitated the functional interpretation of complex trait association signals in previous studies (Nica et al , ).…”
Section: Discussionmentioning
confidence: 99%